A carbon-free polyoxometalate molecular catalyst with a cobalt–arsenic core for visible light-driven water oxidation. Issue 61 (7th July 2016) - Chen, Wei-Chao; Wang, Xin-Long; Qin, Chao; Shao, Kui-Zhan; Su, Zhong-Min; Wang, En-Bo
Abstract : Na12 [{Co II 7 As III 6 O9 (OH)6 }(A-α-SiW9 O34 )2 ]·8H2 O with the first reported cobalt–arsenic core was synthesized, thoroughly characterized and employed to catalyze water oxidation under visible-light-driven conditions. Abstract : A carbon-free, stable, homogeneous water oxidation catalyst based on the unique hepta-nuclear cobalt–arsenic core ("fused" double-quasi-cubane) and polyoxometalate ligands, Na12 [{Co II 7 As III 6 O9 (OH)6 }(A-α-SiW9 O34 )2 ]·8H2 O (1), was synthesized, thoroughly characterized and employed to catalyze water oxidation under visible-light-driven conditions.